Sharia-Based Transformational Leadership and Employee Loyalty: The Mediating Role of Psychological Empowerment in Indonesian Public Sector Organizations - Tamriatin Hidayah; Hamzah Fansuri Yusuf; Pawestri Winahyu (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
Employee loyalty has become an increasingly important challenge in Indonesian public sector organizations, particularly among non-civil servant employees who experience employment insecurity, limited career advancement opportunities, and disparities in organizational benefits. Although transformational leadership has been widely recognized as a determinant of employee loyalty, limited empirical evidence explains how Sharia-Based Transformational Leadership, grounded in Islamic ethical values, influences employee loyalty through psychological empowerment. This study aims to examine the direct effects of Sharia-Based Transformational Leadership, compensation, and perceived organizational support on employee loyalty and psychological empowerment, as well as the mediating role of psychological empowerment. A quantitative explanatory design was employed using survey data collected from 477 non-civil servant employees in local government organizations in Jember Regency, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Sharia-Based Transformational Leadership, compensation, and perceived organizational support significantly enhance psychological empowerment and employee loyalty. Psychological empowerment also serves as a significant mediator between the antecedent variables and employee loyalty. These findings extend Social Exchange Theory by integrating Islamic ethical leadership principles and suggest that strengthening Sharia-based leadership practices, equitable compensation, and organizational support can foster sustainable employee loyalty in Indonesian public sector organizations.